A Review on Medicinal Characteristics of Pomegranate (Punica granatum L.) - A Sarkhosh; Z Zamani; R Fatahi; H Ghorbani; J Hadian (Institue of Medicinal Plants, ACECR, 2007)
Pomegranate (Punica granatum L.) is a deciduous shrub and native to Iran having ancient culture in this country and Iran is one of the biggest producers of pomegranate in the world. This fruit is used in traditional medicine because of its antibacterial, anti-inflammatory, and alleviative characteristics. Extracts of different parts of pomegranate fruit is rich in phenolic compounds and its rind extract and seed oil have vigorous antioxidant activity. Elagic acid is one of the most important phenolic compound with antioxidant activity, present in the pomegranate rind extract. Inhibitory effect of pomegranate seed oil on breast and skin cancer has been reported. Use of seed oil and extracts of different parts of pomegranate fruit has been considered in production of phytostrogenic compounds. At the present time, the fruit of pomegranate besides its use as a fruit and having nutritional value is also considered for its pharmaceutical characteristics. This paper is a review on articles and different sources in order to get more familiarity with medicinal characteristics of this fruit.